Public awareness on the importance of using paper bags: a case study in Siburan / Macmarchirello Edwin Jemat - Jemat, Macmarchirello Edwin (2007)
The purpose of this study is to identify the awareness level of the public in Siburan on the importance of using paper bags. By determining the awareness level, it will assist in preparing modes to overcome the problems that affect the level of awareness through some comments and recommendation given by the respondents. In addition, this study will measure the knowledge of the public towards green conscious. The results of this study emphasizes on the driver factors that influence society awareness. It is also revealed that the total awareness from respondent’s perspective towards the importance of using paper bags.